+0

# Quadratic Formula??

0
372
2

Consider the system

−8x − 12y = 36
5y − 6x = 41

Find x.

Guest Jun 3, 2014

### Best Answer

#2
+18829
+5

(1) -8x - 12y = 36  ->   8x + 12y = -36

(2)  5y -   6x = 41  ->  -6x +   5y =  41

$$\boxed{\begin{array}{rcrcr} 8x & + & 12y &=& -36 \\ -6x & + & 5y &=& 41 \end{array}}$$

\boxed{\begin{array}{rcrcr}
8x & + & 12y &=& -36 \\
-6x & + & 5y &=&  41
\end{array}}

$$\\x= \frac{\begin{vmatrix} -36 & 12 \\ 41 & 5 \end{vmatrix}}{\begin{vmatrix} 8& 12 \\ -6 & 5 \end{vmatrix}} =\frac{-36*5-41*12}{8*5-(-6)*12} =\frac{-180-492}{40+72} =\frac{-672}{112}=-6\\ \boxed{x=-6} \\y= \frac{\begin{vmatrix} 8 & -36 \\ -6 & 41 \end{vmatrix}}{\begin{vmatrix} 8& 12 \\ -6 & 5 \end{vmatrix}} =\frac{8*41-(-6)(-36)}{8*5-(-6)*12} =\frac{328-216}{40+72} =\frac{112}{112}=1\\ \boxed{y=1}$$

\\x=
\frac{\begin{vmatrix}
-36 & 12 \\
41 & 5
\end{vmatrix}}{\begin{vmatrix}
8& 12 \\
-6 & 5
\end{vmatrix}}
=\frac{-36*5-41*12}{8*5-(-6)*12}
=\frac{-180-492}{40+72}
=\frac{-672}{112}=-6\\
\boxed{x=-6}
\\y=
\frac{\begin{vmatrix}
8 & -36 \\
-6 & 41
\end{vmatrix}}{\begin{vmatrix}
8& 12 \\
-6 & 5
\end{vmatrix}}
=\frac{8*41-(-6)(-36)}{8*5-(-6)*12}
=\frac{328-216}{40+72}
=\frac{112}{112}=1\\
\boxed{y=1}

heureka  Jun 4, 2014
Sort:

### 2+0 Answers

#1
+81014
+5

−8x − 12y = 36
-6x +  5y  = 41         We can use the elimination method to solve this

We'll eliminate "x"   by multiplying the top equation by -6 on both sides and by multiplying the bottom equation by 8 on both sides   .....this gives us

48x + 72y = -216

-48x + 40y = 328       Now....add the equations together

112y = 112                So...it's clear that y = 1

To find "x,"  substitute 1 for y in any of the equations....I'll use -6x + 5y = 41

-6x + 5(1) = 41

-6x + 5 = 41        subtract 5 ftom both sides

-6x = 36             divide by -6 on both sides

x = -6

So....x = -6 and y = 1......you should verify that these "work" in the other equations...I think you will find that they do......

CPhill  Jun 3, 2014
#2
+18829
+5
Best Answer

(1) -8x - 12y = 36  ->   8x + 12y = -36

(2)  5y -   6x = 41  ->  -6x +   5y =  41

$$\boxed{\begin{array}{rcrcr} 8x & + & 12y &=& -36 \\ -6x & + & 5y &=& 41 \end{array}}$$

\boxed{\begin{array}{rcrcr}
8x & + & 12y &=& -36 \\
-6x & + & 5y &=&  41
\end{array}}

$$\\x= \frac{\begin{vmatrix} -36 & 12 \\ 41 & 5 \end{vmatrix}}{\begin{vmatrix} 8& 12 \\ -6 & 5 \end{vmatrix}} =\frac{-36*5-41*12}{8*5-(-6)*12} =\frac{-180-492}{40+72} =\frac{-672}{112}=-6\\ \boxed{x=-6} \\y= \frac{\begin{vmatrix} 8 & -36 \\ -6 & 41 \end{vmatrix}}{\begin{vmatrix} 8& 12 \\ -6 & 5 \end{vmatrix}} =\frac{8*41-(-6)(-36)}{8*5-(-6)*12} =\frac{328-216}{40+72} =\frac{112}{112}=1\\ \boxed{y=1}$$

\\x=
\frac{\begin{vmatrix}
-36 & 12 \\
41 & 5
\end{vmatrix}}{\begin{vmatrix}
8& 12 \\
-6 & 5
\end{vmatrix}}
=\frac{-36*5-41*12}{8*5-(-6)*12}
=\frac{-180-492}{40+72}
=\frac{-672}{112}=-6\\
\boxed{x=-6}
\\y=
\frac{\begin{vmatrix}
8 & -36 \\
-6 & 41
\end{vmatrix}}{\begin{vmatrix}
8& 12 \\
-6 & 5
\end{vmatrix}}
=\frac{8*41-(-6)(-36)}{8*5-(-6)*12}
=\frac{328-216}{40+72}
=\frac{112}{112}=1\\
\boxed{y=1}

heureka  Jun 4, 2014

### 14 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details